PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION( STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SDN 001 PANGKALAN KASAI KECAMATAN SEBERIDA - Sumiarti, Marda Laila; Alim, Jesi Alexander; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac : The purpose alms of this research was to improve science learning outeomes of the second grade students At SDN 001 Pangkalan Kasai , The Academic year 2014 / 2015, the subject of this research were the second grade students at SDN 001 Pangkalan Kasai, with 27 Studentd as population, this research was class action research by using 2 cycles. Based on the data of this research the learning outcomes of the students was merease. In the first cycles the average of teacher’s activity was 68,74 %. In the second cycles has inerensed with average 83,33 %. Beside that, for the student’s activity in first cycles was 64’50 %, in the second cycles the students activity was merease with average 83,33 %. The outcomes of this research always increase in every cycles. Before teacher using cooperative learning by students team achievement division (STAD),the student who can achieve the learning just II students (40,74 %) with average 62,22 %. After teacher did activity in the first cycles the total of student who can achieve the learning of 17 students (62,96 %), with average 68,51 %, in the second cycles the total student in crease of students learning outcomes was 20,75 %, So it can conclude that in this hyphoyhesis the application of cooperatife learning by using student team achievement Division (STAD) can increase the students selence learning outcomes of the second grade student at SDN 001 Pangkalan Kasai, can accepted.Keyword : cooperative learning mode I Student Team Achievenent Division (STAD), sclence learning outcomes.